Defining adaptive capacity in healthcare: A new framework for researching resilient performance. (September 2020) - Anderson, J.E.; Ross, A.J.; Macrae, C.; Wiig, S.
Abstract: Resilience principles show promise for improving the quality of healthcare, but there is a need for further theoretical development to include all levels and scales of activity across the whole healthcare system. Many existing models based on engineering concepts do not adequately address the prominence of social, cultural and organisational factors in healthcare work. Promising theoretical developments include the four resilience potentials, the CARE model and the Moments of Resilience Model, but they are all under specified and in need of further elaboration. This paper presents the Integrated Resilience Attributes Framework in which these three theoretical perspectives are integrated to provide examples of anticipating, responding, monitoring and learning at different scales of time and space. The framework is intended to guide researchers in researching resilience, especially the linkages between resilience at different scales of time and space across the whole healthcare system. Highlights: Theoretical development of resilient healthcare is needed to include activity across the whole healthcare system. The resilience potentials, the CARE model and the Moments of Resilience model are promising but need development. The Integrated Resilience Attributes Framework defines resilience concepts across the whole healthcare system. The framework can help to focus research questions and investigate resilience at different scales of time and space.